(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The morphology of some structures of legs and last urites, useful for discriminating the subgenera of the genera Bombus and Psithyrus is examined. This work completes previous researches of the same Authors, where other characteristics of morphology, particularly females’ head and males’ genitalia, were analyzed, in order to draw up a dichotomic key that summarizes the parameters considered till now.